Representation of Bullying Issues in Joe Bell Film (Roland Barthes Semiotics Analysis) - Ricky Ramadhan, Dhimas (Jogjakarta Communication Conference (JCC), 2023)
Bullying is an act of hurting someone that is carried out continuously without any compassion that occurs in society. The representation of the issue of bullying can be seen in several films. One of the films that discuss bullying is the film